Prognostic value of γ‐glutamyltransferase‐to‐albumin ratio in patients with pancreatic ductal adenocarcinoma following radical surgery. (10th January 2019) - Li, Shuo; Xu, Huaxiang; Wu, Chuntao; Wang, Wenquan; Jin, Wei; Gao, Heli; Li, Hao; Zhang, Shirong; Xu, Jinzhi; Zhang, Wuhu; Xu, Shuaishuai; Li, Tianjiao; et al.
Abstract : We created a novel ratio index, γ‐glutamyltransferase‐to‐albumin ratio (GAR), based on preoperative liver function test of patients with pancreatic ductal adenocarcinoma (PDAC). Preoperative GAR is an independent prognostic factor for prediction of surgical outcomes in PDAC patients. Combination of TNM stage, GAR, preoperative serum CA19‐9, and tumor differentiation can enhance the prognostic accuracy. Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a devastating malignancy with poor prognosis. Many preoperative biomarkers can predict postoperative survival of PDAC patients. In this study, we created a novel ratio index based on preoperative liver function test, γ‐glutamyltransferase‐to‐albumin ratio (GAR), and evaluated its prognostic value in predicting clinical outcomes of PDAC patients following radical surgery. We retrospectively enrolled 833 PDAC patients who had underwent radical surgery at our institution between January 2010 and January 2017. Patients were divided into two groups according to the cut‐off value of GAR. Univariate and multivariate survival analysis between the groups were evaluated. TNM stage, GAR, preoperative serum carbohydrate antigen 19‐9 (CA19‐9) and tumor differentiation were combined to generate a more accurate prognostic model. The optimal cut‐off value of GAR was 0.65. Significant correlations were found between GAR and tumor location, tumor size, vascular invasion, obstructive jaundice, biliary drainage and parameters of liver function test. Univariate and multivariate analysis showed that high level of GAR independently predicted poorer postoperative overall survival (OS, P < 0.001) and recurrence‐free survival (RFS, P < 0.001). Subgroup analysis demonstrated that GAR was predictive of survival in patients without biliary obstruction or severely impaired liver function. In addition, integration of GAR, preoperative serum CA19‐9, and tumor differentiation into TNM staging system could better stratify the prognosis for PDAC patients compared with TNM stage alone. Our study demonstrates that preoperative GAR is an independent prognostic factor for prediction of surgical outcomes in PDAC patients. Combination of TNM stage, GAR, preoperative serum CA19‐9, and tumor differentiation can enhance the prognostic accuracy.